DER TROST DER POESIE: STIFTERS ABDIAS. (October 2015) - Lauer, Gerhard; Cooper, Ian; Holmes, Deborah
ABSTRACT Stifter's 'Erzählungen' belong to a metaphysically oriented tradition of narration which does not share the modern notion of aesthetic autonomy. Instead art has a moral duty to scrutinise the human heart and to console it in its limitations. With reference to the story Abdias, this essay examines Stifter's narrative techniques of moral explication, exemplification and inculcation, which grant his short stories a strong moral sense. The essay shows how Stifter intimately connected art with the purpose of moral education and sensual pleasure. In this aim, Stifter is not modern. He is, however, modern in the way his stories emphasise subjective perspective and a form of insight only to be achieved through art. That is why his stories belong to a specific type of metaphysical and moral narration within modernity. Stifters Erzählungen gehören einer Tradition des metaphysischen Erzählens an, die das Autonomiepostulat moderner Kunst nicht teilt. Unverstellt hat Kunst die moralphilosophische Aufgabe, das menschliche Herz zu erkunden und in seinen Beschränkungen zu trösten. Am Beispiel der Abdias‐Erzählung untersucht der Aufsatz Stifters Verfahren der moralischen Explikation, Exemplifikation und Einübung, die seinen Erzählungen offensiv Sinn verleihen. Wie der Aufsatz zeigt, bindet Stifter damit die Kunst an Zwecke expliziter Lehrhaftigkeit und die Erzeugung sinnlichen Vergnügens zurück. Mit diesem Anspruch ist Stifter nicht modern. Modern ist er dagegen dort, wo seine Erzählungen die subjektive Perspektive und die nur durch die Kunst zu vermittelnde Erkenntnis betonen. Darin gehört er einem eigentümlich lehrhaften Typus metaphysisch‐moralischen Erzählens in der Moderne an. Für Wolfgang Frühwald zum 80. Geburtstag